1997
DOI: 10.1542/peds.99.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Tubefeeding and Mortality in Children With Severe Disabilities and Mental Retardation

Abstract: We hypothesize that the increased mortality associated with tubefeeding may be attributable to a differential increase in pulmonary disease secondary to overly vigorous nutritional maintenance and subsequent aspiration after tube placement. For children with tracheostomy this risk may be reduced. If tracheostomy proves to be associated with a relatively more favorable outcome for tubefeeding, we hypothesize that it would reflect the benefits of tracheostomy in allowing access to the airway for suctioning and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 23 publications
1
48
0
1
Order By: Relevance
“…Mobile patients are also less likely to have severe contractures, chest wall deformities, or scoliosis, which, when present, contribute to reduced ventilatory function [44][45][46]. Mobile patients are more likely to be fed orally than by gastrostomy tube and, as the present study and other studies [26] have demonstrated, oral feeding is associated with improved survival.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Mobile patients are also less likely to have severe contractures, chest wall deformities, or scoliosis, which, when present, contribute to reduced ventilatory function [44][45][46]. Mobile patients are more likely to be fed orally than by gastrostomy tube and, as the present study and other studies [26] have demonstrated, oral feeding is associated with improved survival.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, we could not directly compare the results of this study to our earlier studies of severely disabled children [26] or to children in a persistent [4] or permanent [17] VS. However, a comparison of the Kaplan-Meyer survival curves in these previous studies reveals that the patients in the current study have had a longer survival.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations